EKSPERIMENTASI MODEL PEMBELAJARAN CO-OP-CO-OP TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI MINAT BELAJAR SISWA - Ade Susanti (Mat-Edukasia, 2019)
This study aims to describe the mathematical communication skills taught by the cooperative learning model in Co-o-Co-op terms of high, medium, and low learning interests better than conventional learning. This study uses a quantitative approach and an experimental method with a 2 × 3 factorial design. The data collection technique uses a descriptive test of mathematical communication skills and student learning interest questionnaires. Data analysis using t-test. based on the results of the analysis it was found that mathematical communication skills taught by thetype cooperative learning model Co-o-Co-op were better than conventional learning. If observed from students 'interest in learning, students' mathematical communication skills with interest in learning were in the experimental class better than the control class. Whereas for high and low learning interests in both the experimental class and the control class mathematical communication skills are not as good or the same for interaction data analysis, it was found that there were interactions between students 'learning interests and learning models in influencing students' mathematical communication skills. Keywords: Co-op-Co-op Learning Model, Mathematical Communication Ability, Learning Interest